Johnny Half-Breed, American Indian Identity as a Communion with Animals and Nature - Brendan Firth (Caliban: French Journal of English Studies)
Tribal societies have been considered archaic savages, between animals and civilised man. This stems from a culture fighting against nature, whereas American Indians view themselves as having a specific place in the world, as brothers to the animals in nature. This perspective, admitting a closeness to animals but reversing the judgement to be positive, became an identity battle upholding the agency of American Indians, who, indeed, needed to valorise their ways of life and integration in natural society in order to defend their sovereignty and self-determination. Peter La Farge's song, “Johnny Half-Breed,” presents this perspective in a folk protest song. “Johnny Half-Breed” shows a positive, mythical, and heroic outcast Indian hero, who is at one with the animals in nature but rejected by people of the city, proves his value and affirms his stance in favour of the animals he loves, and of humanity towards the Other.